TRADEMARK AND VALUE ADDITION IN STARTUPS: SUGGESTIONS WITH RESPECT TO INDIA - Shruti Misra, (International Journal of Innovations in Engineering Research and Technology, 2021)
Although avoided by several organizations throughout the initial stages as a further expanse, logos are extremely vital for any organization because it becomes necessary for them to possess a separate face within the market once the needle starts to purpose towards the profit mark. Specifically, for virtual businesses who don't own a brick and mortar workplace, the whole price resides within the look and feel of their online presence (ie. website), and name of the corporate, creating logos extraordinarily necessary for such businesses. In this research paper, a study is made on the importance of trademark in every field. The value addition done by trademark is highlighted with the issues faced.  The study on the suggestions to the various issues of trademark is highlighted. Moreover, the research paper deals with few known case laws and examples in the field of value addition done by trademark.